2006
DOI: 10.1111/j.1365-2036.2006.02897.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of naproxen on gastric acid secretion and gastric pH

Abstract: SUMMARY BackgroundThe mechanisms for the non-steroidal anti-inflammatory drug-induced inflammation in the stomach are unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Different studies showed a direct relation between acid and GI injuries induced by NSAIDs, in fact the main prescribed drugs to prevent such injuries are the proton-pump inhibitors (PPI) [36,37], Fornai suggests that beneficial effects of PPIs on mucosal injury are likely to be independent from the COX-2/PGE 2 /VEGF pathway [38] so considering all the involved cellular pathways it can be deduced that the intact mucus layer protects epithelium from the action of acid pepsin, protons, [H+] and, in addition, when the barrier is damaged, acid aggravates gastric injuries. There are also evidences of an increased basal gastric acid concentration mediated by NSAIDs due to the basal gastric fluid volume reduction [39].…”
Section: Figurementioning
confidence: 99%
“…Different studies showed a direct relation between acid and GI injuries induced by NSAIDs, in fact the main prescribed drugs to prevent such injuries are the proton-pump inhibitors (PPI) [36,37], Fornai suggests that beneficial effects of PPIs on mucosal injury are likely to be independent from the COX-2/PGE 2 /VEGF pathway [38] so considering all the involved cellular pathways it can be deduced that the intact mucus layer protects epithelium from the action of acid pepsin, protons, [H+] and, in addition, when the barrier is damaged, acid aggravates gastric injuries. There are also evidences of an increased basal gastric acid concentration mediated by NSAIDs due to the basal gastric fluid volume reduction [39].…”
Section: Figurementioning
confidence: 99%
“…In humans, NSAID‐induced acute gastric injury has been shown to be greater in volunteers who had the lowest fasting pH following naproxen administration 24 . Naproxen has been demonstrated to reduce total gastric acid volume with concomitant increase in gastric acid concentration in humans 25 . Funatsu et al.…”
Section: Systemic Effectsmentioning
confidence: 99%
“…This review concluded that most studies showed that indomethacin does not affect basal acid secretion, but some showed that it increased histamine‐stimulated secretion [28] . Subsequent studies seem to support these conclusions [29,30] . Thus, it might appear that NSAIDs have some, albeit relatively minor, effects on gastric acidity in humans.…”
Section: Resultsmentioning
confidence: 99%